2002
DOI: 10.1104/pp.004770
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Phospholipid Metabolism in Arabidopsis. Characterized and Putative Isoforms of Inositol Phospholipid Kinase and Phosphoinositide-Specific Phospholipase C

Abstract: Phosphoinositides (PIs) constitute a minor fraction of total cellular lipids in all eukaryotic cells. They fulfill many important functions through interaction with a wide range of cellular proteins. Members of distinct inositol lipid kinase families catalyze the synthesis of these phospholipids from phosphatidylinositol. The hydrolysis of PIs involves phosphatases and isoforms of PI-specific phospholipase C. Although our knowledge of the roles played by plant PIs is clearly limited at present, there is no dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
390
0
18

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(410 citation statements)
references
References 150 publications
2
390
0
18
Order By: Relevance
“…the PX-PH PLDs, plants possess an additional subfamily, namely the C2 PLDs. Interestingly, the opposite seems to be true for the phosphoinositide-specific phospholipase C (PLC) family, which consists of five classes in animals and is restricted to one class in plants (Cockcroft, 2006;Mueller-Roeber and Pical 2002). Moreover, phosphatidic acid (PA) seems to play a central role in plant PLD and PLC signaling, whereas diacylglycerol (DAG) appears to be the prominent second messenger in animal PLD and PLC signaling events.…”
Section: Chaptermentioning
confidence: 99%
“…the PX-PH PLDs, plants possess an additional subfamily, namely the C2 PLDs. Interestingly, the opposite seems to be true for the phosphoinositide-specific phospholipase C (PLC) family, which consists of five classes in animals and is restricted to one class in plants (Cockcroft, 2006;Mueller-Roeber and Pical 2002). Moreover, phosphatidic acid (PA) seems to play a central role in plant PLD and PLC signaling, whereas diacylglycerol (DAG) appears to be the prominent second messenger in animal PLD and PLC signaling events.…”
Section: Chaptermentioning
confidence: 99%
“…Of the other three putative OsPIPKs, two of them, OsPIPK2 and OsPIPK8, are truncated peptides that lacked the N-terminus and the other, OsPIPK6, lacks the corresponding EST sequence in the database. In another model plant, Arabidopsis, there are 11 genes encoding PIPK proteins, which are highly similar to AtPIP5K1 [33], and only two proteins lack the MORN motifs. However, whether these two putative AtPIPKs are expressed is at present unclear, as no mRNA or EST sequences have been reported for either of them [33].…”
Section: Presence Of Multiple Morn Motifs In Ospipk1 As Well As Othementioning
confidence: 99%
“…In another model plant, Arabidopsis, there are 11 genes encoding PIPK proteins, which are highly similar to AtPIP5K1 [33], and only two proteins lack the MORN motifs. However, whether these two putative AtPIPKs are expressed is at present unclear, as no mRNA or EST sequences have been reported for either of them [33]. Structural organization Figure 3A).…”
Section: Presence Of Multiple Morn Motifs In Ospipk1 As Well As Othementioning
confidence: 99%
“…Two major types (termed II and III) of PtdIns 4-kinases have been identified in animals and plants. At2g40850 encodes a type II PtdIns 4-kinase, which has been previously named PI4Kg1 (Mueller-Roeber and Pical, 2002). While the function of type II PtdIns 4-kinases in plants is unknown, it has been suggested that in animals, they are involved in the regulation of intracellular trafficking (Wang et al, 2003;Salazar et al, 2005).…”
Section: Identification Of Novel Regulators Of Microsporogenesismentioning
confidence: 99%